2020
DOI: 10.1186/s12974-020-02025-7
|View full text |Cite
|
Sign up to set email alerts
|

CCN3 is dynamically regulated by treatment and disease state in multiple sclerosis

Abstract: Background Multiple sclerosis (MS) is an immune-mediated disease that damages myelin in the central nervous system (CNS). We investigated the profile of CCN3, a known regulator of immune function and a potential mediator of myelin regeneration, in multiple sclerosis in the context of disease state and disease-modifying treatment. Methods CCN3 expression was analysed in plasma, immune cells, CSF and brain tissue of MS patient groups and control subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…In an EAE model of MS, CCN5 mRNA was found to be significantly upregulated in spinal cord tissue, but as the tissue was collected in end-stage disease, its relevance to early-stage disease in MS is questionable (23). Interestingly, a significant positive correlation has been reported between levels of the related protein CCN3 in matched plasma and CSF of MS patients, which was absent in a comparator group of idiopathic intracranial hypertension patients (24). CCN3 plays various roles in the immune system and CCN5 and CCN3 have been reported to have antagonistic effects (25).…”
Section: Discussionmentioning
confidence: 99%
“…In an EAE model of MS, CCN5 mRNA was found to be significantly upregulated in spinal cord tissue, but as the tissue was collected in end-stage disease, its relevance to early-stage disease in MS is questionable (23). Interestingly, a significant positive correlation has been reported between levels of the related protein CCN3 in matched plasma and CSF of MS patients, which was absent in a comparator group of idiopathic intracranial hypertension patients (24). CCN3 plays various roles in the immune system and CCN5 and CCN3 have been reported to have antagonistic effects (25).…”
Section: Discussionmentioning
confidence: 99%
“…Serum CCN3 concentrations were elevated in RA patients and positively correlated with expression of IL-6 [35]. CCN3 expression was increased in SSc, multiple sclerosis patients [36,37]. For osteoarthritis, CCN3 could inhibit PI3K/AKT/mTOR pathway by reducing HMGB1 levels and decrease extracellular matrix catabolism [38].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies almost focused on exploring the effects of CCN3 on animal models and in vitro experiment. Recent studies provide more and rich data from clinical samples [ 52 , 64 , 71 , 73 ]. Although CCN3 targeted therapy has not been used in clinical immune diseases, we believe that the application of the anti-CCN2 antibody in clinical trials will contribute to further clinical research of CCN3 to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…A recent data from clinical samples showed that the serum CCN3 level was positively correlated with the CSF CCN3 level. In addition, the CCN3 mRNA expression was higher in peripheral immune cells (PBMC) of MS patients compared with the healthy control group [ 71 ]. Therefore, the myelin regeneration function of Tregs and CCN3 can be offered as potential encouraging treatment prospects for multiple sclerosis, while further experiments should be performed to address the mechanism.…”
Section: The Roles Of Ccn3 Protein In Immune-related Diseasesmentioning
confidence: 99%